Evaluation of Environmental Radioactivity in Thessaly after Storm Daniel: A Pilot Study - Karpouza, Evgenia; Gelatsoras, Foivos Panagiotis; Siltzovalis, Georgios; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2026)
The level of radioactivity is examined in regions of Thessaly affected by disastrous floods after storm Daniel in September 2023. The purpose of this study is to map the specific radioactivity of natural isotopes (40K, 232Th and 238U-series) and of the artificial isotope 137Cs in the affected areas. Twenty surface soil samples were collected from undisturbed locations, free of agricultural or urban activity, approximately a year after the floods. Following standard sample preparation, measurements were conducted with high-resolution gamma-ray spectroscopy using a High-Purity Germanium (HPGe) detector at the γSPEC laboratory of the National and Kapodistrian University of Athens (NKUA). The results are illustrated on maps, while and values for the absorbed doses of ionizing radiation and the external hazard indices were calculated using UNSCEAR models.